Penyalahgunaan Sistem Pembayaran Online oleh Seorang Gamers Mobile Legend - M. Riyan Musytary (Bandung Conference Series: Law Studies, 2022)
Abstract. A payment platform is a payment system that uses the internet as a means of intermediary for the transfer. Various new modus operandi of crimes emerged due to misuse on online platforms, one of which was in the case of No. 1054/Pid.Sus/2019/PN Jkt.Pst. Fund transfer crime, namely a series of activities starting with an order from the Originator with the aim of transferring a certain amount of funds to the Beneficiary mentioned in the Funds Transfer Order until the receipt of the funds by the Beneficiary. Therefore, it is necessary to implement strict and clear criminal law enforcement by law enforcement officers. This approach method is normative juridical, namely carrying out an inventory of positive laws regarding criminal law enforcement against abuse on online platforms. This type of research is qualitative research, namely data collection with the intention of interpreting the phenomenon of payment abuse on online platforms to the detriment of the Bank. The research specification is descriptive analysis, which examines criminal law enforcement against the misuse of payments on online platforms intentionally associated with Law Number 3 of 2011 concerning Fund Transfers. The purpose of this study is to find out the enforcement of criminal law against misuse on online platforms that intentionally causes bank losses in terms of Law Number 3 of 2011 concerning Fund Transfers; and To find out the judge's considerations in the decision of the Central Jakarta District Court No. 1054/Pid.Sus/2019/PN Jkt.Pst related to the provisions of criminal law. The results of the study show that criminal law enforcement against intentional abuse on online platforms in online game item top up payment portals by gamers, in this case Yane Septiani who has harmed the bank, can be threatened by Article 85 of the Funds Transfer Act, because in the case of it has fulfilled the criminal elements in the provisions of the article; The judge's consideration in Decision No. 1054/Pid.Sus/2019/PN Jkt.Pst only granted the indictment based on article 362 of the Criminal Code regarding theft. In fact, this incident can also be threatened using Article 85 of the Criminal Code because the crime committed in this case has fulfilled the criminal elements contained in Article 85 of the Funds Transfer Law. Abstract Platform pembayaran merupakan sistem pembayaran meggunakan internet sebagai sarana perantara transfer tersebut. Berbagai macam modus operandi kejahatan baru muncul akibat penyalahgunaan di platform online, salah satunya dalam kasus No.1054/Pid.Sus/2019/PN Jkt.Pst. Tindak pidana transfer dana, yaitu rangkaian kegiatan yang dimulai dengan perintah dari Pengirim Asal yang bertujuan memindahkan sejumlah dana kepada Penerima yang disebutkan dalam Perintah Transfer Dana sampai dengan diterimanya dana oleh Penerima. Oleh karena itu perlu dilaksanakannya penegakan hukum pidana yang tegas dan jelas oleh aparat penegak hukum. Metode pendekatan ini adalah yuridis normative, yaitu melakukan inventarisasi hukum positif tentang penegakan hukum pidana terhadap penyalahgunaan di platform online. Jenis penelitian ini adalah penelitian kualitatif, yaitu pengumpulan data dengan maksud menafsirkan fenomena penyalahgunaan pembayaran di platform online hingga merugikan pihak Bank. Spesifikasi penelitian adalah deskriptif analisis, yaitu mengkaji penegakan hukum pidana terhadap penyalahgunaan pembayaran di platform online secara sengaja yang dikaitkan dengan Undang-Undang Nomor 3 Tahun 2011 tentang Transfer Dana. Tujuan penelitian ini adalah Untuk mengetahui Penegakan Hukum Pidana terhadap penyalahgunaan di platform online secara sengaja yang menimbulkan kerugian bank di tinjau dari Undang-Undang Nomor 3 Tahun 2011 Tentang Transfer Dana; dan Untuk mengetahui pertimbangan hakim dalam putusan Pengadilan Negeri Jakarta Pusat No.1054/Pid.Sus/2019/PN Jkt.Pst dikaitkan dengan ketentuan hukum pidana. Hasil penelitian menunjukan bahwa Penegakan Hukum Pidana terhadap penyalahgunaan di platform online secara sengjaa di portal pembayaran top up item permainan secara online oleh seorang gamers yang dalam kasus ini yaitu Yane Septiani yang telah merugikan pihak bank dapat diancam oleh Pasal 85 UU Transfer Dana, karena dalam kasus ini telah memenuhi unsur-unsur pidana dalam ketentuan pasal tersebut; Pertimbangan Hakim dalam Putusan No.1054/Pid.Sus/2019/PN Jkt.Pst hanya mengabulkan dakwaan berdasarkan pasal 362 KUHP tentang pencurian saja. Sedang sesungguhnya peristiwa ini pun bisa diancam menggunakan Pasal 85 KUHP karena tindak pidana yang dilakukan dalam kasus ini telah memenuhi unsur-unsur pidana yang terkandung dalam Pasal 85 UU Transfer Dana.